Policing opinions: elites, science and popular opinion - Beaud, Paul (Javnost (Ljubljana), 1999)
Different socio-historical conceptualisations of the emergence of public opinion in the eighteenth century, which have given rise to the works of Habermas about the public sphere, in particular, allow us to think about the actual social referent of the public opinion phenomenon. The classical focus on prerevolutionary, enlightened public opinion and the hypothetical causal effect of the Enlightenment conceal the anthropological invariants of opining as a procedure of sharing differences and individual interests. This "intello-centric" approach reproduces the elitist ideology in this analysis that limits the procedural universality to the pseudo-public sphere of the "true" citizens, although it declares, as a matter of principle, that all citizens ought to participate in government. After having proven the segregating stakes in these processes, the article shows that the concept of public opinion is not reduced to a normative definition -- either in the cultivated sense of a rational discussion or in the psycho-sociological sense of an aggregation of individual states of mind -- by the community of scholarsand politicians. It also refers to the common opinion and the popular form of speech which characterise the "doxastic" community of mutual knowledge that ordinary actors hold, or think they hold, about each other.
Keywords: javnost; javno mnenje; communication; komuniciranje; social psychology; socialna psihologija; zgodovinski pregledi